Statistical significance of prognostic factors on the progression of chronic kidney disease through simulation study - Alka Sabharwal; Gurprit Grover; Shrawan Kumar (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: Chronic kidney disease (CKD) is a serious public health problem. It affects 10% to 16% of adults around the world. In India, the approximate prevalence is 800 per million population (pmp) and incidence of end-stage renal disease (ESRD) is 150 -200 pmp. Objectives: To evaluate the differences in the impact of prognostic factors for the progression of CKD into higher stages using appropriate and robust tests. Materials and Methods: Permutation test and likelihood ratio test were applied to ascertain the statistical significance of the prognostic factors for the progression of CKD into higher stages. The data consists of 100 non-hospitalized CKD patients of three stages namely stage 2, stage 3 and stage 4. A simulation study has been carried out to determine the power of permutation test and likelihood ratio test testing the significance of difference between the values of the parameters of the distribution of prognostic factors involved in the progression of CKD in stage 2, stage 3 and stage 4. Results: Permutation test and likelihood ratio test based on our data set suggest that serum creatinine, urea, hemoglobin, albumin and age are the significant factors for the progression of CKD to higher stages. Conclusion: Under various health conditions using simulation study, all the factors included in the study are responsible for the progression of the disease.